2015
DOI: 10.2965/jwet.2015.335
|View full text |Cite
|
Sign up to set email alerts
|

Potential Utilization of Pineapple Waste Streams for Polyhydroxyalkanoates (PHAs) Production via Batch Fermentation

Abstract: This study involves the production of a value-added product of polyhydroxyalkanoates (PHAs) from pineapple cannery wastes by isolated bacterial strain of Bacillus sp. SV13 via batch fermentation process. Two carbon sources, glucose and sucrose, were used to investigate the potential of PHAs production compared to when the agro-industrial waste was used. Batch fermentation was performed in a flask scale under controlled conditions: 37°C, and 200 rpm of agitation rate. The PHAs concentration [g/L], biomass in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…1, and the filtrate was collected and finally adjusted pH to 7.0 to obtain pineapple peel hydrolysate (PPH) containing fermentable sugars. The compositions and concentration of the sugars in PPH were analyzed using highperformance liquid chromatography (HPLC) with refractive index detector (RID), Zorbax NH 2 column, mobile phase: acetonitrile/water (75−25% v/v) and flow rate of 1.5 ml/min (high-performance liquid chromatograph, Agilent Technologies, 1200 series, USA) [2,12]. Additionally, the presence of amino acids and essential minerals in PPH were analyzed by HPLC and Inductively Coupled Plasma Optical Emission spectroscopy (ICP-OES), respectively as described by standard procedures.…”
Section: Pretreatment and Hydrolysis Of Pineapple Peel Waste (Ppw)mentioning
confidence: 99%
See 2 more Smart Citations
“…1, and the filtrate was collected and finally adjusted pH to 7.0 to obtain pineapple peel hydrolysate (PPH) containing fermentable sugars. The compositions and concentration of the sugars in PPH were analyzed using highperformance liquid chromatography (HPLC) with refractive index detector (RID), Zorbax NH 2 column, mobile phase: acetonitrile/water (75−25% v/v) and flow rate of 1.5 ml/min (high-performance liquid chromatograph, Agilent Technologies, 1200 series, USA) [2,12]. Additionally, the presence of amino acids and essential minerals in PPH were analyzed by HPLC and Inductively Coupled Plasma Optical Emission spectroscopy (ICP-OES), respectively as described by standard procedures.…”
Section: Pretreatment and Hydrolysis Of Pineapple Peel Waste (Ppw)mentioning
confidence: 99%
“…Briefly, 500 µl of cell-free supernatant was added to 500 µl of the color reagent. These solutions were heated in boiling water for 10 min and immediately transferred on ice, and the absorbance was measured at 540 nm when the calibration curve was glucose at 0 to 1.0 g/l [2,12].…”
Section: Total Reducing Sugar (Trs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have reported the potential use of pineapple waste in producing PHAs. Earlier, Suwannasing et al [15] reported that pineapple cannery wastes were used to produce PHAs. The produced PHAs were analysed using Fourier Transform Infra-Red (FTIR), and the results showed that the PHAs were present in the form of polyhydroxybutyrate (PHB).…”
Section: Bio-packagingmentioning
confidence: 99%
“…Considering its characteristics, composition and health benefits, pineapple waste contains proteolytic enzyme for bromelain production [11] and phenolic compound which is a good antioxidant source including antimicrobial and anticancer properties [12]. Pectin, lignin, cellulose and their derivatives from pineapple waste are the major components needed in producing nanocellulose and green packaging [13][14][15]. Since pineapple waste is a good carbon source, organic acid [16], wine [17], vinegar [18], dye adsorbent [19], biofuel [20][21][22] and biogas [23][24][25] can be produced from it.…”
Section: Introductionmentioning
confidence: 99%